National Trends and Impact of Acute Kidney Injury Requiring Hemodialysis in Hospitalizations With Atrial Fibrillation - Lili Chan; Swati Mehta; Kinsuk Chauhan; Priti Poojary; Sagar Patel; Sumeet Pawar; Achint Patel; Ashish Correa; Shanti Patel; Pranav S. Garimella; Narender Annapureddy; Shiv Kumar Agarwal; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atrial fibrillation (AF) is a common cause for hospitalization, but there are limited data regarding acute kidney injury requiring dialysis (AKI‐D) in AF hospitalizations. We aimed to assess temporal trends and outcomes in AF hospitalizations complicated by AKI‐D utilizing a nationally representative database. Methods and Results Utilizing the Nationwide Inpatient Sample, AF hospitalizations and AKI‐D were identified using diagnostic and procedure codes. Trends were analyzed overall and within subgroups and utilized multivariable logistic regression to generate adjusted odds ratios (aOR) for predictors and outcomes including mortality and adverse discharge. Between 2003 and 2012, 3751 (0.11%) of 3 497 677 AF hospitalizations were complicated by AKI‐D. The trend increased from 0.3/1000 hospitalizations in 2003 to 1.5/1000 hospitalizations in 2012, with higher increases in males and black patients. Temporal changes in demographics and comorbidities explained a substantial proportion but not the entire trend. Significant comorbidities associated with AKI‐D included mechanical ventilation (aOR 13.12; 95% CI 9.88‐17.43); sepsis (aOR 8.20; 95% CI 6.00‐11.20); and liver failure (aOR 3.72; 95% CI 2.92‐4.75). AKI‐D was associated with higher risk of in‐hospital mortality (aOR 3.54; 95% CI 2.81‐4.47) and adverse discharge (aOR 4.01; 95% CI 3.12‐5.17). Although percentage mortality within AKI‐D decreased over the decade, attributable risk percentage mortality remained stable. Conclusions AF hospitalizations complicated by AKI‐D have quintupled over the last decade with differential increase by demographic groups. AKI‐D is associated with significant morbidity and mortality. Without effective AKI‐D therapies, focus should be on early risk stratification and prevention to avoid this devastating complication.